The near-complete genome assembly of pickling cucumber and its mutation library illuminate cucumber functional genomics and genetic improvement - Yao Tian; Kui Li; Tonghui Li; Wudi Gai; Jie Zhou; Xing Wang Deng; Yan Xue; Yun Deng; Hang He; Xingping Zhang (Molecular Plant, 2025)

Upcycling of wool keratin for selective recovery of gold from aqueous solution - Zixiang Chen; Yumei Chen; Tonghui Xu; Yuanlong Guo; Tianlong He; Haibo Xie; Lihua Zhang (Chemical Engineering Journal, 2025)

Farmland phytoremediation in bibliometric analysis - Chaoqun Wang; Lirong Deng; Yongxiang Zhang; Mingtao Zhao; Meiqi Liang; Lien-Chieh Lee; Chicaiza-Ortiz Cristhian; Long Yang; Tonghui He (Journal of Environmental Management, 2024)

Asymmetric pre-growing season warming may jeopardize seed reproduction of the sand-stabilizing shrub Caragana microphylla - Hongjiao Hu; Xinping Liu; Yuhui He; Yuqiang Li; Tonghui Zhang; Yuanzhi Xu; Jiaqi Jing (Science of The Total Environment, 2023)

A phytoexclusion strategy for reducing contamination risk of rice based on low-Cd natural variations pyramid of root transporters - Yan Huili; Liu Ruoxi; Peng Zhimei; Zhang Hezifan; Hao Shuangnan; Guo Hanyao; Wang Binghan; Wang Weiping; Yu Yijun; Zhang Hongliang; Qian Tonghui; Xu Wenxiu; et al. (Journal of Hazardous Materials, 2023)

Higher atmospheric evapotranspiration demand intensified drought in semi‐arid sandy lands, northern China - Hongjiao Hu; Xinping Liu; Yuhui He; Tonghui Zhang; Yuanzhi Xu; Lilong Wang (International Journal of Climatology, 2023)
Drought seriously endangers the development of agro‐pastoral ecotone in arid and semi‐arid regions. However, drought evolution characteristics of semi‐arid sandy grassland and its drivers are not well understood in the complex climate change context. Thus, in this paper, the revised standardized precipitation evaporation indices on one‐month (SPEI‐1) and growing‐season (SPEI‐6) scale, flash drought and dry spells (DS) were calculated as drought indicators, and the temporal variabilities and meteorological drivers of drought in Horqin Sandy Land during the growing period (April–September) from 2007 to 2021 were studied. The results showed that SPEI‐1 and SPEI‐6 exhibited negative trends and periodic change. This drought aggravation was manifested in increased grades and numbers of drought months. Flash droughts can occur every month during the growing season. And its occurrence was not only positively correlated with all drought events in frequency but also synchronized in time. The increased number of DS showed an asymmetrical shift towards 7‐day‐and‐longer DS. SPEI sensitivity to precipitation (P) was noticeably higher than to atmospheric evapotranspiration demand (AED) at both monthly and growing season scales. SPEI sensitivity to AED was modulated by P amounts, which was higher during low P period. Apart from the amounts of P and AED, their temporal variability also strongly determined how they affect the drought severity. P was also the main driver for flash drought and long DS, but AED with larger amount and higher variability is the reason for their aggravation. Our results demonstrate the complexity of drought intensification in semi‐arid sandy grasslands and highlight the important role of AED anomalies in it.

Effects of soil salinity characteristics on three habitats in inland salt marshes - Qiao Cui; Tonghui He; Anning Zhang; Xiaosai Quan; Yanqiong Feng; Xiangquan Chen; Yushi He (Journal of Plant Research, 2021)

Environmental significance of RSL in ancient city wall: historical desertification of Ordos Plateau, Northern China - Yinzhou Huang; Nai-ang Wang; Tonghui He; Hongyi Chen; Wenyong Feng; Hao Long (Climatic Change, 2009)